Transformation towards the future sustainable: Analysis implementation of carbon tax in ASEAN-5 countries - Mariyani, Endang; Suciati, Ranila (WIM Solusi Prima, 2024)
The emission of carbon dioxide (CO₂), which has an impact on climate change, has now developed into the global problems that impact the whole world and human life. To handle this problem, ASEAN-5, which consists of Indonesia, Malaysia, Singapore, Thailand, and the Philippines, participated in an effort to reduce donation emissions of global carbon through the initiation of tax carbon. Research Objectives This is to describe how ASEAN-5 countries respond, prepare, and make policies for implementing a carbon tax. The initiative to tax carbon in ASEAN-5 is expected to push the transformation of the economy toward sustainability and provide benefits to the economy through efficient energy and innovative technology. Using a scoping review method for various journals and articles research, the study analyzes the approach taken by each ASEAN-5 country in facing the challenge of implementing tax carbon. Study results. This concludes that the only ASEAN-5 country that has applied carbon tax is Singapore, which is still in the preparation and planning stage. Many factors have become inhibitors in implementing the carbon tax in ASEAN-5 countries. A country's dependence on material burn fossils is one of the main factors. Although so, many' green ' efforts have already been implemented by ASEAN-5 countries to help reduce global emissions. This study focuses on factors, inhibitors, and potential benefits to the economy from policy tax on ASEAN-5 carbon, mainly through improved efficiency energy and the development of energy-expected renewables​ that can push the transformation of the economy to sustainability.